A qualitative study into L2 writing strategies of university students - Raoofi, Saeid; Chan, Swee Heng; Mukundan, Jayakaran; Md Rashid, Sabariah (Canadian Center of Science and Education, 2014)
This study reports on an investigation into writing strategies of Malaysian university students learning English as a second language. Qualitative data were collected from 21 undergraduate university students aged 19 to 21. The students interviewed reported using a variety of writing strategies. It was also found that all of the participants reported doing some pre-writing activities, and having awareness of their own writing problems. The findings of the study also revealed that the highly proficient student writers reported using more moremetacognitive strategies such as organizing ideas and revising content than less skilled ones. Limitations of the study are discussed, and suggestions for future research are offered. Implications for writing instruction are also presented.